# Answer to Question #16986 in Calculus for Paulinexx

Question #16986

A function is defined as f(x)=x(squared)+3

Find a simplified expression for f(a+2)-f(a-5)

Find a simplified expression for f(a+2)-f(a-5)

Expert's answer

we can write f(a+2)-f(a-5)=(a+2)^2 +3 - ( (a-5)^2+3)=(a+2)^2 -

(a-5)^2=(a+2+a-5)(a+2 -(a-5) )=(2a-3)*7=14a-21

(a-5)^2=(a+2+a-5)(a+2 -(a-5) )=(2a-3)*7=14a-21

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment